Some problems of policies of direct financial supports for science and technology activities by enterprises, 2011-2015 period - Giang, Dang Thu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Direct financial supports for enterprises to conduct science and technology (S&T) activities are one of financial policy tools in use actually in Vietnam. The supports target to stimulate enterprises to make investment for S&T activities. Over the world, particularly in developed countries, the direct financial supports is the State policy tool which is used largely to share costs with enterprises and to stimulate enterprises to make more investments for S&T activities. International experience showed that this policy is designed in conformity to economic context and innovation system in every development stage of the nation. It would give contributions to push up effectively innovation activities, particularly in enterprise sector. In this paper, the author will provide a view on direct financial supports by the State for S&T activities by enterprises and show some remaining problems in regulations by these policies in Vietnam Code: 17091301